Nutracêuticos imunomoduladores com potencial uso clínico para cães e gatos - Zaine, Leandro; Monti, Mariana [UNESP]; Vasconcellos, Ricardo Souza; Carciofi, Aulus Cavalieri [UNESP] (My University, 2014)
The use of nutraceuticals in veterinary medicine is growing and is assumed that they could aid in clinical treatment. This review aims to describe some nutraceuticals that act on the immunity of dogs and cats and show the possible benefits as an adjuvant treatment for some diseases. The action of some yeast derivates as immunomodulators, especially the beta-glucan fraction, was already proved to occur in dogs and cats, being beneficial as an adjuvant therapy in many clinical conditions. Omega-3 polyunsatured fatty acids, possibly the mostly used nutraceuticals, can improve the condition in some diseases, such as hypertension, renal, cardiac, gastrointestinal and autoimmune diseases, arthritis and cancer. Vitamin E has antioxidant and immunomodulatory action and can aid in the treatment of dermatologic and hepatobiliar conditions. The use of carotenoids, which have similar action to vitamin E, can be of interest for being potent antioxidants and might be helpful for enhancing immune response against microorganisms and also act preventing tumors. Despite it are still needed clinical trials to better understand the real benefits of nutraceuticals supplementation in each specific disease, the comprehension of the mechanisms by which they act indicates they are promising for clinical use.
Immunomodulatory nutraceuticals with potential clinical use for dogs and cats
Keywords: Beta-glucan; Carotenoids; Immunity; Omega-3 polyunsatured fatty acids; Vitamin E